2020
DOI: 10.3390/v12020173
|View full text |Cite
|
Sign up to set email alerts
|

The Susceptibility of Human Melanoma Cells to Infection with the Leningrad-16 Vaccine Strain of Measles Virus

Abstract: Oncolytic viruses, including live attenuated measles virus (MV) vaccine strains, have recently been shown as promising therapeutic agents against human malignancies. In this study, the oncolytic potential of the attenuated vaccine strain Leningrad-16 (L-16) of MV was evaluated in a panel of human metastatic melanoma cell lines. The L-16 measles virus was shown to replicate within melanoma cells mediating direct cell killing of tumor cells, although all melanoma cell lines varied in regard to their ability to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
0
9
0
1
Order By: Relevance
“…Meanwhile, preclinical efficacy of oncolytic MeV has been demonstrated against a broad range of cancer entities (reviewed in [ 18 ]). In addition to Edmonston B derivatives, also the vaccine strains Moraten-Schwarz [ 19 ], Edmonston-Zagreb and AIK-C [ 20 ], rMV-Hu191 [ 21 ], as well as Leningrad-16 [ 22 ] have been shown to exert oncolytic effects in preclinical studies.…”
Section: Introduction—measles Virus For Cancer Therapymentioning
confidence: 99%
“…Meanwhile, preclinical efficacy of oncolytic MeV has been demonstrated against a broad range of cancer entities (reviewed in [ 18 ]). In addition to Edmonston B derivatives, also the vaccine strains Moraten-Schwarz [ 19 ], Edmonston-Zagreb and AIK-C [ 20 ], rMV-Hu191 [ 21 ], as well as Leningrad-16 [ 22 ] have been shown to exert oncolytic effects in preclinical studies.…”
Section: Introduction—measles Virus For Cancer Therapymentioning
confidence: 99%
“…It was concluded that type I IFN responses determine whether melanoma cells are sensitive or resistant to MV. Furthermore, the MV Leningrad-16 (L-16) strain showed replication in a panel of human metastatic melanoma cell lines and mediated cell killing in tumor cells [ 110 ]. MV L-16 generated statistically significant inhibition of tumor growth in a melanoma xenograft model.…”
Section: Vaccines Against Cancermentioning
confidence: 99%
“…The collect-and-screen approach in the field of OVs has been widely used for various virus strains and in vitro tumor cell models (see, for example, [15][16][17][18]). It should be noted that the topicality and employability of this approach is still justifiable [19].…”
Section: Diversity Of Viruses As the Basis For The Development Of New Ovsmentioning
confidence: 99%